Energy transition leadership in Malaysia - Syed Abdull Aziz Jailani, Sharifah Shaza (2025)
This study aimed to evaluate the effectiveness of the current leadership situation in Malaysia to drive energy transition using the New Model of Leadership for Change by Roger Gill (2003) as benchmark. A semi-structured interview was employed involving professionals from the Malaysian energy industry. Information gathered were analysed using thematic analysis method which is by identifying recurring themes and patterns, which was then compared against the New Model of Leadership for Change. The findings suggest the model effectively outlines the essential leadership qualities required to drive Malaysia’s energy transition. It highlights the importance of visionary thinking, strategic thinking, good values and culture and the ability to inspire and motivate the people. However, the model could be significantly enhanced by incorporating an element of risk-taking. This addition would demonstrate a leader's strong commitment and willingness to achieve transformative change, showing a higher level of dedication and a proactive approach to overcoming challenges. Malaysian leaders have shown commendable progress in developing a vision and high-level strategy for the country’s energy transition by setting ambitious targets but other critical components such as strategic planning, fostering values and culture, empowerment of teams, and sustaining motivation and inspiration have yet to be demonstrated.